2003
DOI: 10.1007/s11664-003-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quaternary additions on thermoelectric properties of TiNiSn-based half-heusler alloys

Abstract: Half-Heusler-type compounds have gained increasing attention as promising thermoelectric materials. In the present work, a focus is placed on TiNiSn with additions of Hf, Zr, Si, or Pt. Nominally stoichiometric TiNiSn alloys were prepared using arc melting and subsequent annealing at 1,073 K for 2 weeks. The thermoelectric properties, such as thermoelectric power, electrical resistivity, and thermal conductivity, were measured in a temperature range from 300 K to 1,000 K. As-cast materials show metallic transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 7 publications
5
57
0
1
Order By: Relevance
“…The of TiCoSb, ZrCoSb and HfCoSb are larger than those of as-cast samples reported in the previous study. 11) It is well known that the annealing condition 10,[13][14][15] and the deviation from the stoichiometric composition 6) have much effect on the thermoelectric properties of the half-Heusler compounds. For example, the of TiCoSb tends to increase with decreasing the Co/Sb ratio and with increasing the Ti/Sb ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The of TiCoSb, ZrCoSb and HfCoSb are larger than those of as-cast samples reported in the previous study. 11) It is well known that the annealing condition 10,[13][14][15] and the deviation from the stoichiometric composition 6) have much effect on the thermoelectric properties of the half-Heusler compounds. For example, the of TiCoSb tends to increase with decreasing the Co/Sb ratio and with increasing the Ti/Sb ratio.…”
Section: Resultsmentioning
confidence: 99%
“…So, TiCoSb is expected to have a larger thermoelectric power S. From the literatures, [6][7][8][9][10][11] TiCoSb has a negative thermoelectric power. The improvement of the structural disorder 12) by annealing has been reported on MNiSn system [13][14][15] and TiCoSb system. 10) The thermoelectric properties of ZrCoSb and HfCoSb have been reported only for the electrical resistivity and thermoelectric power below room temperature.…”
Section: Introductionmentioning
confidence: 93%
“…Surprisingly, the attempts made to reduce its lattice thermal conductivity are found to have less effect on its PF due to its low carrier mobility [8], and thus the possible improvement of ZT is expected. In 2003, Katayama et al [2] reported an upper limit ZT=0.  by alloying the ternary half-Heusler alloys.…”
Section: T S Zt mentioning
confidence: 99%
“…The increase in thermal conductivity at high temperatures is mainly due to the remarkable increase in electronic contribution. It is well-known that TiNiSn-based half-Heusler alloys always exhibit maximum ZT around 700-800 K [2,3,7]. The reason is that the maximum power factor and lowest thermal conductivity occur simultaneous ly at high temperature.…”
mentioning
confidence: 99%
“…The substitution in each site is very useful for improvement of thermoelectric properties, because the position of the Fermi level in the gap can be controlled and the lattice thermal conductivity reduces due to enhancement of the phonon scattering. Since the half-Heusler compounds with 18 valence electrons have the narrow band gap near the Fermi level and show the large thermoelectric power, (Ti, Zr, Hf)NiSn, [1][2][3][4][5][6][7] (Ti, Zr, Hf)CoSb [8][9][10][11] and other half-Heusler compounds have been studied as advanced thermoelectric materials. Although high performance n-type materials in the half-Heusler compounds have been reported, 4,6) such p-type thermoelectric materials have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%